“To Have a Winning Way of a Russian Name About Us.” Conversation Between Ambassador Extraordinary and Plenipotentiary M. Konarovsky and Ambassador Extraordinary and Plenipotentiary A. Kuznetsov Featuring V. Vorotnikov and A. Сhechevishnikov - М. A. Konarovsky; A. I. Kuznetsov (Международная аналитика)
This publication is the record of a conversation in the editorial office of the International Analytics Journal about the peculiarities of the diplomatic service in various states, due to the historical traditions of the state service as a whole; about the training of diplomats in Russia in the past and present, and about the requirements for young diplomats. Among the most important requirements: learning how to formulate analytical texts, participating in the drafting of diplomatic documents; the ability to speak and conduct public polemics in English and in the language of the host country; constantly broadening cultural horizons, being an interesting conversationalist; observing the everyday and behavioural restrictions imposed by the diplomatic service; assuming all the nuances of diplomacy. The publication also analyses the main problem of diplomatic training at MGIMO – the need to maintain a university level of education while spending a significant part of the study time on language training.